Stability of electrolyzed water: from the perspective of food industry - Khalid,, N. I.; Sulaiman, N. S; Ab Aziz, N.; Taip, F. S.; Sobri, S.; Nor-Khaizura, M. A. R. (Rynnye Lyan Resources, 2021)
Green cleaner and disinfectant can provide a better environment and they can reduce cleaning cost by eliminating the cost of harsh cleaning chemicals, minimizing cleaning chemicals storage space, reducing cost for wastewater treatment and reducing logistics cost for chemical supply. This study explored the personal view of Small and Medium Enterprises (SMEs) top to bottom workers towards the challenges during cleaning and disinfection process and their readiness in accepting a green cleaner and disinfectant. In this work, the advantages and disadvantages of electrolyzed water (EW) as green cleaner and disinfectant were discussed. A lab-scale batch ion-exchange membrane electrolysis unit was used to produce acidic electrolyzed water (AcEW) and alkaline electrolyzed water (AlEW). The stability of AcEW and AlEW was also studied based on its physical changes (pH, oxidative-reduction potential (ORP), chlorine content and hydrogen peroxide content) in 7 days of storage, whereby measurements were taken daily. The pH maintained for both AcEW and AlEW during the 7 days of storage. The ORP maintained at plateau for the first 5 days of AcEW storage. After 5 days, AcEW showed a decreasing trend. While ORP for AlEW increases drastically between day 1 and 2. Then, the ORP reaches a plateau after three days. The amount of free chlorine, total chlorine and hydrogen peroxide content was 10 mg/L, respectively, on the day of production. However, all the properties decreased gradually and there were no chlorine and hydrogen peroxide detected on the 7th day. The results from this study can be used as a guideline to store the EW and to understand the stability of the EW, which can benefit the SME food manufacturers.